Intracranial Mesenchymal Chondrosarcoma: A Case Report - Prachi Agrawal; Ajay Gupta; Shagun Juneja; Veena Gupta (Indian Journal of Neurosurgery)
Abstract Primary intracranial mesenchymal chondrosarcoma is an extremely rare tumor. We present a case of primary intracranial mesenchymal chondrosarcoma in a young female who presented with headache, loss of vision, and one episode of convulsions associated with nausea and vomiting. MRI brain revealed a large, well-marginated, lobulated, partially calcified, intensely enhancing lesion with a broad dural base in bilateral frontal regions with marked mass effect suggestive of meningioma. Bilateral frontal craniotomy with gross tumor excision was performed. Histopathology revealed mesenchymal chondrosarcoma. Adjuvant radiotherapy was delivered and patient is currently on follow-up. We emphasize that intracranial mesenchymal chondrosarcoma is a rare neoplasm and should be considered in the differential diagnoses of intracranial mass along with meningioma. Treatment of choice is surgery followed by adjuvant radiotherapy. We review the relevant literature and discuss the characteristics of this rare tumor.